Preparation method of iron-doped polymer self-assembled nano-particles and nano-particles prepared by same
By preparing iron-doped polymer self-assembled nanoparticles, using the self-assembly characteristics of the polymer chain and the mechanism of the delocalization of excited state electrons to generate free radicals, the problems of difficulty and high cost of preparation of existing nanoenzymes are solved, and the preparation of nanoparticles with high catalytic oxidation performance is achieved, which is suitable for a variety of application fields.
Patent Information
- Application Number
- CN202311345938.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-16
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-10-16
AI Technical Summary
Existing natural enzymes and most nanoenzymes have problems such as volatile, high cost, difficult preparation, and inability to produce on a large scale, making it difficult to meet the needs of high catalytic oxidation performance.
By preparing iron-doped polymer self-assembled nanoparticles, using the self-assembly characteristics of the polymer chain to bring iron ions into the nanoparticles, and free radicals are generated by delocalizing excited state electrons, combining trivalent iron ions to form a Fenton-like catalytic oxidation system to achieve oxidation of organic matter.
The preparation of self-assembled nanoparticles of iron-based polymers with high catalytic oxidation performance has the advantages of stable structure, adjustable catalytic capacity, no need for strong acids and alkalis, and is green and environmentally friendly. It is suitable for photocatalysis, bactericidal and antibacterial fields, etc.
Smart Images

Figure CN119842085A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a method for preparing iron-doped polymer self-assembled nanoparticles and the prepared nanoparticles, belonging to the field of functional nanomaterials. Background Art
[0002] In recent years, many studies have reported that carbon nanomaterials have high catalytic oxidation capabilities similar to natural enzymes, and can be used as substitutes for natural enzymes in biomedicine and other fields. Catalytic oxidation refers to an oxidation reaction carried out by a catalyst using air, oxygen, ozone, etc. as oxidants under certain pressure and temperature conditions. However, natural enzymes and most nanozymes have problems such as variability, high cost, difficulty in preparation, and inability to mass produce. Therefore, seeking a new material for catalytic oxidation nanozymes that is simple to synthesize, high yield, and high activity has become a new research hotspot.
[0003] Metal-doped polymer self-assembled nanoparticles can be used as a new type of nanozyme to solve this problem. They greatly improve the catalytic oxidation performance by exposing more active sites. Self-assembly refers to the spontaneous formation of a structure with unique characteristics through the interaction between molecules, so that a single molecule forms a directional and ordered structure. The units are orderly connected through non-covalent bonds to form an assembly with a specific structure or function. At present, it has shown great application potential in the fields of biomedicine and environmental testing. Summary of the invention
[0004] On the one hand, the polymer chains of iron-based polymer self-assembled nanoparticles can self-assemble through the interaction of hydrogen bonds and van der Waals forces, bringing iron ions into the self-assembled body. On the other hand, electron delocalization can occur in the excited state, and the generated free radicals (superoxide anion radicals, hydroxyl radicals, etc.) can be captured by trivalent iron ions and reduced to divalent iron ions to form a Fenton-like catalytic oxidation system to achieve the oxidation of organic matter near the nanoparticles. Therefore, metal-doped polymer self-assembled nanoparticles have great application value in the fields of photocatalytic degradation, bacterial detection, bactericidal and antibacterial, food preservation, wound healing, etc.
[0005] According to one aspect of the present application, a method for preparing iron-doped polymer self-assembled nanoparticles is provided, comprising the following steps:
[0006] The mixed solution containing the polymer, the iron salt and the solvent I is mixed with the solvent II to obtain the iron-doped polymer self-assembled nanoparticles.
[0007] The molecular weight of the polymer is 7000 to 15000 Da;
[0008] The end-capping group of the polymer is a carboxyl group;
[0009] The polymer contains pendant carboxyl groups.
[0010] The iron salt is selected from at least one of ferric chloride, ferric nitrate and ferric sulfate;
[0011] The solvent I is selected from at least one of DMSO, methanol, ethanol, water and acetone;
[0012] The mass ratio of the polymer to the iron salt is 1:0.1-50;
[0013] The mass ratio of the polymer to the solvent I is 0.01 to 1:10
[0014] The solvent II is selected from at least one of ethanol, chloroform, acetone, acetonitrile, toluene and n-hexane;
[0015] The volume ratio of the solvent II to the mixed solution is 0.1 to 1:10
[0016] The polymer is obtained by the following method:
[0017] The following steps are involved:
[0018] Mixing polycarboxylic acid and polyamine, reacting, and drying to obtain the non-conjugated dehydrated polymer;
[0019] The polycarboxylic acid is selected from at least one of oxalic acid, trisaccharic acid, succinic acid, 1,2,4-butanetricarboxylic acid, 1,2,3,4-butanetetracarboxylic acid, glutaric acid, adipic acid, and 1,2,4,5-cyclohexanetetracarboxylic acid;
[0020] The polyamine is selected from at least one of ethylenediamine, propanetriamine, 1,3-propylenediamine and phenylenediamine;
[0021] The reaction temperature is 80-260°C;
[0022] The reaction atmosphere is an inert gas atmosphere.
[0023] The molar ratio of the polycarboxylic acid to the polyamine is 1:10 to 10:1.
[0024] The reaction is a melt polymerization reaction.
[0025] The reaction time is 0.5 to 6 hours.
[0026] The inert gas atmosphere is selected from at least one of nitrogen, helium and argon.
[0027] The polymer is a non-conjugated dehydrated polymer with a molecular weight of 1000-15000Da.
[0028] Optionally, the polymer is selected from at least one of poly N-(3-phenyl)-2-carboxymethylimide-succinimide, poly N-ethyl-2-carboxymethylimide-succinimide, polyphenyl oxalic acid diimide, polyethyl oxalic acid diimide, polyethyl glutaric acid diimide, polyphenyl glutaric acid diimide, polyethyl succinic acid diimide, and polyphenyl succinic acid diimide.
[0029] Specifically,
[0030] A low molecular weight non-conjugated polyimide having a self-assembly function and carboxylic acid groups as side groups and end groups is dispersed with trivalent iron ions in a first solvent and stirred uniformly;
[0031] The second solvent is gradually added until precipitation is generated, and the obtained precipitate is filtered and dried to obtain iron-based polymer self-assembled nanoparticles with catalytic oxidation performance.
[0032] According to another aspect of the present application, there is provided an iron-doped polymer self-assembled nanoparticle prepared by the above-mentioned method for preparing the iron-doped polymer self-assembled nanoparticle.
[0033] The imide of the polymer and the carbonyl oxygen of the carboxylic acid can be complexed with iron ions in the first solvent. When the second solvent is added, self-assembly occurs due to the interaction between hydrogen bonds and van der Waals forces between polymer chains, bringing iron ions into the self-assembly to form iron-based polymer self-assembled nanoparticles. The principle of catalytic oxidation is that the self-assembled non-conjugated polyimide can undergo electron delocalization in the excited state. When there are trivalent iron ions nearby, the generated free electrons can be captured by the trivalent iron ions to generate divalent iron ions. The valence state of the trivalent iron ions complexed with the carboxyl group in the self-assembled nanoparticles remains unchanged. At this time, divalent iron, trivalent iron and unbound imide exist in the self-assembled nanoparticles at the same time, forming a Fenton-like catalytic oxidation system to achieve the oxidation of organic matter near the nanoparticles.
[0034] According to another aspect of the present application, there is provided an application of the above-mentioned iron-doped polymer self-assembled nanoparticles for use in the fields of photocatalysis, bactericidal and antibacterial.
[0035] The beneficial effects of this application include:
[0036] (1) The preparation method is simple, low cost, short cycle and high yield;
[0037] (2) The iron-doped polymer self-assembled nanoparticles have a stable structure, adjustable catalytic oxidation ability, and do not require the use of strong acids or bases, making them green and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is the XRD pattern of the product nanoparticles in Example 1.
[0039] Figure 2a This is a scanning electron microscope image of the nanoparticles in Example 1, with a scale of 25 μm.
[0040] Figure 2b This is the XRF mapping image of the nanoparticles in Example 1, with a scale of 25 μm.
[0041] Figure 3 This is the absorption spectrum of the oligomer in Example 1 when the iron-doped nanoparticles coexist with tetramethylbenzidine (TMB).
[0042] Figure 4 The control group is the gel without (left) and with (right) iron-doped nanoparticles after 15 days of storage. DETAILED DESCRIPTION
[0043] The present invention will be further described below in conjunction with embodiments so that those skilled in the art can better understand the present invention, but the present invention is not limited thereto.
[0044] Example 1
[0045] 0.2 g of poly (N-(3-phenyl)-2-carboxymethylimide-succinimide) with an average molecular weight of 8000 Da was dissolved in 3 mL of water at room temperature and stirred evenly. Then 0.7 g of ferric chloride was added and stirring was continued. Then 50 mL of acetonitrile was added to produce precipitation. The precipitate was filtered and dried to obtain iron-based polymer self-assembled nanoparticles with catalytic oxidation properties.
[0046] 1.0 mg of the nanoparticles was added to 2.0 mL of 100 mg / mL 3,3 , ,5,5 , -tetramethylbenzidine hydrochloride in an aqueous solution, the solution quickly turns blue, indicating that the obtained nanoparticles have good oxidizability.
[0047] Figure 1 The XRD spectrum of the nanoparticles produced in Example 1. It can be seen from the figure that doping does not change the amorphous nature of the nanoparticles, and iron is dispersed inside the nanoparticles in the form of ions rather than oxides.
[0048] Figure 2a This is a scanning electron microscope image of the nanoparticles in Example 1, with a scale of 25 μm. It can be seen from the image that the nanoparticles can be deposited relatively evenly on the silicon wafer.
[0049] Figure 2b This is the iron element topology of the nanoparticles in Example 1, with a scale of 25 μm. It can be seen from the figure that the iron ions are evenly distributed in the nanoparticle layer.
[0050] Figure 3This is the absorption spectrum of the oligomer and iron-doped nanoparticles coexisting with tetramethylbenzidine (TMB) in Example 1. It can be seen from the figure that iron doping can effectively oxidize TMB to increase its absorbance
[0051] Figure 4 The figure shows the comparison of gelatin gel without (left) and with (right) iron-doped nanoparticles after 15 days of storage. It can be seen from the figure that the presence of iron-doped nanoparticles produces superoxide radicals, which can effectively inhibit the growth of bacteria in gelatin.
[0052] Example 2
[0053] 0.2 g of poly (N-ethyl-2-carboxymethylimide-succinimide) with an average molecular weight of 8000 Da was dissolved in 3 mL of dimethyl sulfoxide (DMSO) at room temperature and stirred evenly. Then 0.8 g of ferric nitrate was added and stirring was continued. Then 30 mL of ethanol was added to produce a precipitate. The precipitate was filtered and dried to obtain iron-based polymer self-assembled nanoparticles with catalytic oxidation properties.
[0054] 1.0 mg of the nanoparticles was added to 2.0 mL of 100 mg / mL 3,3 , ,5,5 , -tetramethylbenzidine hydrochloride in an aqueous solution, the solution quickly turns blue, indicating that the obtained nanoparticles have good oxidizability.
[0055] Example 3
[0056] 0.3 g of polyphenyl oxalic acid diimide with an average molecular weight of 7000 Da was dissolved in 5 mL of methanol at room temperature and stirred evenly. Then 0.6 g of ferric sulfate was added and stirring was continued. Then 30 mL of toluene was added to produce precipitation. The precipitate was filtered and dried to obtain iron-based polymer self-assembled nanoparticles with catalytic oxidation properties.
[0057] 1.0 mg of the nanoparticles was added to 2.0 mL of 10 mg / mL 3,3 , ,5,5 , -tetramethylbenzidine hydrochloride in an aqueous solution, the solution quickly turns blue, indicating that the obtained nanoparticles have good oxidizability.
[0058] Example 4
[0059] 0.3 g of polyethylene oxalic acid diimide with an average molecular weight of 7000 Da was dissolved in 5 mL of ethanol at room temperature and stirred evenly. Then 0.5 g of ferric sulfate was added and stirring was continued. Then 50 mL of chloroform was added to produce precipitation. The precipitate was filtered and dried to obtain iron-based polymer self-assembled nanoparticles with catalytic oxidation properties.
[0060] 1.0 mg of the nanoparticles was added to 2.0 mL of 100 mg / mL 3,3 , ,5,5 , -tetramethylbenzidine hydrochloride in an aqueous solution, the solution quickly turns blue, indicating that the obtained nanoparticles have good oxidizability.
[0061] Example 5
[0062] At room temperature, 0.2 g of polyethylglutaric acid diimide with an average molecular weight of 7500 Da was dissolved in 3 mL of acetone and stirred evenly. Then, 0.7 g of ferric sulfate was added and stirring was continued. Then, 30 mL of n-hexane was added to produce a precipitate. The precipitate was filtered and dried to obtain iron-based polymer self-assembled nanoparticles with catalytic oxidation properties.
[0063] 1.0 mg of the nanoparticles was added to 2.0 mL of 100 mg / mL 3,3 , ,5,5 , -tetramethylbenzidine hydrochloride in an aqueous solution, the solution quickly turns blue, indicating that the obtained nanoparticles have good oxidizability.
[0064] Example 6
[0065] 0.2 g of polyphenylglutaric acid diimide with an average molecular weight of 7500 Da was dissolved in 3 mL of ethanol at room temperature and stirred evenly. Then 0.6 g of ferric nitrate and chloride was added and stirring was continued. Then 30 mL of acetone was added to produce precipitation. The precipitate was filtered and dried to obtain iron-based polymer self-assembled nanoparticles with catalytic oxidation properties.
[0066] 1.0 mg of the nanoparticles was added to 2.0 mL of 100 mg / mL 3,3 , ,5,5 , -tetramethylbenzidine hydrochloride in an aqueous solution, the solution quickly turns blue, indicating that the obtained nanoparticles have good oxidizability.
[0067] Example 7
[0068] 0.2 g of poly(ethyl succinic acid diimide) with an average molecular weight of 8000 Da was dissolved in 5 mL of dimethyl sulfoxide (DMSO) at room temperature and stirred evenly. Then 0.5 g of ferric chloride was added and stirring was continued. Then 50 mL of ethanol was added to produce a precipitate. The precipitate was filtered and dried to obtain iron-based polymer self-assembled nanoparticles with catalytic oxidation properties.
[0069] Take 2.0 mg of the nanoparticles and add them to 2.0 mL of 100 mg / mL 3,3 , ,5,5 ,-tetramethylbenzidine hydrochloride in an aqueous solution, the solution quickly turns blue, indicating that the obtained nanoparticles have good oxidizability.
[0070] Example 8
[0071] 0.3 g of polyphenyl succinic acid diimide with an average molecular weight of 8000 Da was dissolved in 5 mL of methanol at room temperature and stirred evenly. Then 0.3 g of ferric chloride was added and stirring was continued. Then 30 mL of acetonitrile was added to produce precipitation. The precipitate was filtered and dried to obtain iron-based polymer self-assembled nanoparticles with catalytic oxidation properties.
[0072] Take 2.0 mg of the nanoparticles and add them to 2.0 mL of 100 mg / mL 3,3 , ,5,5 , -tetramethylbenzidine hydrochloride in an aqueous solution, the solution quickly turns blue, indicating that the obtained nanoparticles have good oxidizability.
[0073] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing iron-doped polymer self-assembled nanoparticles, characterized in that: The following steps are involved: The mixed solution containing the polymer, the iron salt and the solvent I is mixed with the solvent II to obtain the iron-doped polymer self-assembled nanoparticles.
2. The preparation method according to claim 1, characterized in that: The molecular weight of the polymer is 7000 to 15000 Da; The end-capping group of the polymer is a carboxyl group; The polymer contains pendant carboxyl groups.
3. The preparation method according to claim 1, characterized in that: The iron salt is selected from at least one of ferric chloride, ferric nitrate and ferric sulfate; The solvent I is selected from at least one of DMSO, methanol, ethanol, water and acetone; The mass ratio of the polymer to the iron salt is 1:0.1-50; The mass ratio of the polymer to the solvent I is 0.01 to 1:
10.
4. The preparation method according to claim 1, characterized in that: The solvent II is selected from at least one of ethanol, chloroform, acetone, acetonitrile, toluene and n-hexane; The volume ratio of the solvent II to the mixed solution is 0.1 to 1:
10.
5. The preparation method according to claim 1, characterized in that: The polymer is obtained by the following method: Mixing polycarboxylic acid and polyamine, reacting, and drying to obtain the non-conjugated dehydrated polymer; The polycarboxylic acid is selected from at least one of oxalic acid, trisaccharic acid, succinic acid, 1,2,4-butanetricarboxylic acid, 1,2,3,4-butanetetracarboxylic acid, glutaric acid, adipic acid, and 1,2,4,5-cyclohexanetetracarboxylic acid; The polyamine is selected from at least one of ethylenediamine, propanetriamine, 1,3-propylenediamine and phenylenediamine; The reaction temperature is 80-260°C; The reaction atmosphere is an inert gas atmosphere; The molar ratio of the polycarboxylic acid to the polyamine is 1:10 to 10:1; The reaction is a melt polymerization reaction; The reaction time is 0.5 to 6 hours; The inert gas atmosphere is selected from at least one of nitrogen, helium and argon; The molecular weight of the polymer is 1000-15000 Da. 6 . Iron-doped polymer self-assembled nanoparticles prepared by the method for preparing iron-doped polymer self-assembled nanoparticles according to any one of claims 1 to 5 .
7. A use of the iron-doped polymer self-assembled nanoparticles according to claim 6, characterized in that: Used in the fields of photocatalysis, bactericidal and antibacterial.
Citation Information
Patent Citations
Composite material as well as preparation method and application thereof
CN104497363A
Dry preparation method of transition metal doped carbon fluorescent quantum dot
CN108130076A
Iron-doped polymer nanoparticle as well as preparation method and application thereof
CN110665005A
Polyaniline-loaded copper-iron catalyst material, and preparation method and application thereof
CN111790441A
Hydrophilic zinc-doped magnetic nano material, preparation method thereof and application thereof in biomedicine
CN112603997A